Edukasi Sosial Melalui Kampaye Pentingnya Pendidikan Bagi Masyarakat Malaka Tengah - Erni Raster Klau; Samrid Neonufa; Gallex Simbolon; Ambara S. Mardani; Mariana Ikun R.D Pareira; Reschi V.A Sinlae; Ovin M. Lasi; Ferginia R.A Dikuawao (Universitas Muhammadiyah Jember, 2026)
Malaka Regency, particularly Malaka Tengah District, is a region facing complex educational challenges. High dropout rates, limited access to education, and low public awareness of the importance of education are fundamental issues hampering human resource development in the region. This Community Service (PKM) activity aims to increase awareness and understanding of the urgency of education in the Malaka Tengah community through a planned and structured social campaign. The PKM implementation method uses a Participatory Action Research (PAR) approach, involving active community participation in every stage of the activity, from assessment to evaluation. The target audiences are parents, school-age children, and community leaders in Malaka Tengah District. The results of the activity show a significant increase in community awareness of the importance of education, reflected in their commitment to sending their children to higher education and increased participation in available non-formal education programs. This activity recommends the need for continued campaign programs and strengthened collaboration between universities, local governments, and non-formal education institutions in Malaka Regency.